Analyze of Water Injection Performance Surveillance in “ATHENA” Field - Andi Dewi; Firdaus; Deny Fatryanto (Journal of Earth Energy Engineering, 2022)
To measure the success of waterflood activities, we need evaluation and analysis. To support evaluation and analysis need to be done assessment of well connectivity to the response of injection wells, performance wells with Hall-plot and Voidage Replacement Ratio, and calculate water breakthrough time with method Buckley-Leverret whether according to the actual field. To examine these required supporting data such as field history, production and injection history, fluid level measurement data. The results of the study showed the well ATH-43 less response (poor response) and the well ATH-37 and ATH-33 gave good response (good response) and gain oil obtained by 8,196 barrels. The hall-plot evaluation showed that the well ATH-04 had no formation/normal damage, and the results of the VRR showed the VRR < 1. The results of the calculation of water breakthrough time calculations with actual show the well experiencing breakthrough earlier than the calculation. (Premature breakthrough).